2020
DOI: 10.4103/jehp.jehp_110_20
|View full text |Cite
|
Sign up to set email alerts
|

Family problems associated with conduct disorder perceived by patients, families and professionals

Abstract: INTRODUCTION: Conduct disorder is among the most serious and complex complications in school-aged children. Considering severe problems in the families of children with conduct disorder, this article aimed to investigate such problems in this group. SUBJECTS AND METHODS: This qualitative research was conducted on 23 participants in Tehran, Iran. The study participants were selected by purposive sampling technique. Interviewees consisted of children with conduct disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…The authors found through qualitative interviews that caregiver strain negatively impacted the quality of spousal relationships (Sajadi et al, 2020). For instance, parental relationship issues were almost exclusively associated with the behaviour of a child with CD (Sajadi et al, 2020). Marital infidelity and "emotional divorce" (disconnect) were also reported to be prevalent problems in studied couples (Sajadi et al, 2020).…”
Section: Impact On Caregivers' Relationshipsmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors found through qualitative interviews that caregiver strain negatively impacted the quality of spousal relationships (Sajadi et al, 2020). For instance, parental relationship issues were almost exclusively associated with the behaviour of a child with CD (Sajadi et al, 2020). Marital infidelity and "emotional divorce" (disconnect) were also reported to be prevalent problems in studied couples (Sajadi et al, 2020).…”
Section: Impact On Caregivers' Relationshipsmentioning
confidence: 99%
“…Caregivers and families must navigate potential psychosocial harms, such as conflict, spousal problems and feelings of helplessness, all the while attempting to care for their child/youth with CD and other children (Sajadi et al, 2020).…”
Section: Conduct Disorder: a Review Of The Literature And The Impact On Caregiversmentioning
confidence: 99%
See 3 more Smart Citations